Effect of Light Spectrum, Sucrose Concentration, and 6-Benzyl-aminopurine on In Vitro Adventitious Bulb Formation in Tulipa tarda - Małgorzata Maślanka (Agronomy)
This study presents the optimal light spectrum and medium composition for the in vitro induction of adventitious bulbs in T. tarda Stapf. Bulb scales, used as explants, were cultivated on 100% MS solid media with 3% or 6% sucrose and 0 or 0.5 µM BAP (6-benzyl-aminopurine) under a 16 h photoperiod and different fluorescent light treatments (white, red, blue). Darkness was used as a control. The cultures were maintained at 20 ± 2 °C for 12 weeks. The obtained results revealed that white light combined with 6% sucrose yielded the highest adventitious bulb formation, with an average of 12.1 ± 1.3 bulbs per explant. The bulbs formed directly on the surface of the explants. Red light combined with 3% sucrose and 0.5 µM BAP completely inhibited bulb formation, while darkness promoted leaf development, with a maximum of 1.3 ± 0.1 leaves per bulb, under darkness on medium with 6% sucrose. The addition of BAP, in most cases, was essential for root formation, with a maximum of 2.9 ± 0.6 roots per bulb under the influence of white light. This study demonstrates that it is possible to obtain an effective and efficient method for T. tarda propagation from bulb scales treated with 6% sucrose under white light condition. This method offers the potential for the commercial cultivation of this ornamental species.